2017 International Conference on Rehabilitation Robotics (ICORR) 2017
DOI: 10.1109/icorr.2017.8009405
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of grasp recognition for robotic hand prosthesis control based on sEMG data

Abstract: Control methods based on sEMG obtained promising results for hand prosthetics. Control system robustness is still often inadequate and does not allow the amputees to perform a large number of movements useful for everyday life. Only few studies analyzed the repeatability of sEMG classification of hand grasps. The main goals of this paper are to explore repeatability in sEMG data and to release a repeatability database with the recorded experiments. The data are recorded from 10 intact subjects repeating 7 gras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 20 publications
2
91
0
Order By: Relevance
“…We use a low-pass filter as the pre-processing stage and we feed such filtered signals as input for the recognition algorithms without further feature extraction. Such choice allows us to provide a common processing pipeline for all the considered algorithms and was based on preliminary analysis and literature results showing good performance of similar features such as the mean absolute value [23], [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We use a low-pass filter as the pre-processing stage and we feed such filtered signals as input for the recognition algorithms without further feature extraction. Such choice allows us to provide a common processing pipeline for all the considered algorithms and was based on preliminary analysis and literature results showing good performance of similar features such as the mean absolute value [23], [24].…”
Section: Discussionmentioning
confidence: 99%
“…Significant contribution in this direction was provided by the Ninapro database [23], which collects acquisitions totaling 67 subjects performing up to 52 hand movements. It focuses on gesture and subject variability collecting single day sessions, but the authors recently published an extension with data from 10 subjects performing 7 gestures over 5 days, with 2 sessions per day [24]. The recognition of afternoon sessions when training on morning data shows a decrease in accuracy of 27%.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, they are sensitive to noise. This feature has been previously implemented in surface Electromyography (sEMG) and demonstrated high performance [25], [26]. A Random Forest Classifier was used to determine both the surface pattern of examined material and the size of the detected cracks.…”
Section: B Classification Algorithmmentioning
confidence: 99%
“…These approaches detect muscle contraction patterns as discrete classes to drive function modules [5]. A variety of classi cation algorithms have been implemented and tested to discriminate muscle contraction patterns, such as support vector machines [6], random forest classi ers [7], linear discrimination analysis [8], and convolution neural networks [9]. Earlier pattern recognition approaches operate at xed speed for each function module, whereas recent development has shown that augmenting the speed with the extraction of proportional 'class activation' information in addition to class labels could improve overall performance [10], [11].…”
Section: Introductionmentioning
confidence: 99%